Culturally Sustaining Initial Teacher Education: Developing Student Teacher Confidence and Competence to Teach Indigenous Learners. Issue 3 (3rd July 2019) - Averill, Robin Margaret; McRae, Hiria Stacey
Abstract: This article describes how we prepare teachers to be confident and competent teachers of indigenous Māori learners. Programme components are critiqued in relation to promoting culturally sustaining practice using four dimensions: accommodation, reformation, transformation, and representation. We argue that culturally sustaining teacher education is limited by historically Eurocentric policy and programme design and student teachers' and university faculty members' attitudes, skills, and knowledge. Toward transformative and equitable teaching, we offer an example of cultural partnership in programme development and delivery.